PENGARUH KUALITAS SUMBER DAYA MANUSIA, SISTEM PENGENDALIAN INTERNAL DAN PERENCANAAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Patrecia Linecha Ruhupatty; Susi Dwi Mulyani (STMIK Widuri Jakarta, 2025)
This study aims to examine the influence of Human Resource Quality, Internal Control System with Organizational Commitment as a moderation variable on Budget Absorption. This type of research is quantitative research. The data used in this study is primary data. The population in this study is ASN and Non-ASN Secretariat of the Directorate General of Village Government Development, Ministry of Home Affairs, Republic of Indonesia as many as 141 respondents and the sample of this study is 104 samples. The analysis used is the multiple linear regression analysis method.The results of the analysis in the Hypothesis Test with the Moderated Regression Analysis (MRA) regression analysis showed that the Quality of Human Resources (HR) had a positive effect on Budget Absorption (PA). The Internal Control System (SPI) has no effect on Budget Absorption (PA). Budget Planning (PRA) has a positive influence on Budget Absorption (PA). Organizational Commitment (KO) strengthens the influence of Human Resource Quality (HR) on Budget Absorption (PA). Organizational Commitment (KO) does not strengthen the influence of the Internal Control System (SPI) on Budget Absorption (PA). Organizational Commitment (KO) strengthens the influence of Budget Planning (PA) on Budget Absorption (PA).